Effective Microorganism (EM) from Modified Bioinoculant to Increase Biogas Quantity - Nurweni, Susi; Karno, Karno; Suyanto, Beny (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
The result of the study can be implemented by, of and for the community, as a renewable energy substitution for LPG easily and in reasonable prize